Role of Social Entrepreneurship in Addressing the Plight of Stray Dogs in India - Pandey, Anu (2013)
The paper looks into the emergence of social entrepreneurs in addressing the issues of stray dogs and their plight in the city of Delhi. It primarily focuses on their motivation which led them to start their organisations, their problems in starting and running the organisation and their working with and without the government support. The paper also explores the existing gaps in the area. This is an empirical paper that uses a qualitative and case study based approach for the study. It looks into seven cases of individuals whose life mission has been to alleviate the problems and miseries of stray dogs. The paper tries to understand the complexity of this sector and finds a need for a more robust and strong public private partnership in this area. It concludes with a set of recommendations which seem quite vital for the growth and sustenance of this small yet crucial sector of the Indian society.